Pemanfaatan Teknologi Pertanian dan Pengaruhnya Terhadap Pendapatan Petani - Rusydi, Bahrul Ulum; Rusli, Muh. (ICOR: Journal of Regional Economics, 2022)
The use of agricultural equipment technology is expected to be able to break down productivity and efficiency in the production process of agricultural businesses. The purpose of this study was to determine the effect on farmers' income with land area as the control variable and production yields as the intervening variable. This research was conducted in Maccini Baji Village, Bajeng District, Gowa Regency. For data analysis techniques, this study used descriptive quantitative methods with path analysis. The results showed that land area had a positive and significant effect on rice production, technology had a positive but not significant effect on rice production, and production had a positive and significant effect on farmers' income.